Pengembangan Multimedia Interaktif Pengenalan Salat untuk Meningkatkan Aspek Perkembangan Anak Usia Dini - Marlisa, Lusi; Purnama, Sigit (Jurnal Penelitian, 2018)
The aims of the reaserch was: (1) to know how the development of interactive multimedia in praying introduction; (2) to know the effectiveness of the use of interactive multimedia the introduction of prayer for aspects of  child development in integrated isamic kindergarten Mutiara Banguntapan, Bantul Yogyakarta. The method that used in this research was Research and Development (R&D) R&D used for measuring the feasibility of interactive multimedia product by refering to development style of Borg & Gall through 6 stages of development, namely: (1) potential and problem; (2) data collection; (3) design product; (4) validation product; (5) revision product; (6) trials product. The result of the research showed that: (1) interactive multimedia of prayer introduction was developed based on the development prosedure Borg and Gall. The appropriateness of product based on the validation of media experts and material experts with an overall rating of 3.83 in the good category. So that, can be concluded that multimedia developed was suitable to use in the learning media of prayer introduction, then; (2) Application of multimedia interactive prayer performed on 15 child in the class A2 abu sufyan bin harist, by conducting experimental trials by looking at the effectiveness of the use of interactive multimedia introduction of pre and post prayers on aspects of child development. Average effectiveness before use interactive multimedia introduction prayer on aspects child development 36,54% and Average effectiveness after use interactive multimedia introduction prayer on aspects child development 76,66% with motoric physical development 73,33%,  language 80%, cognitive 80%, social emotional 73,33%. So it can be concluded that by using interactive multimedia the introduction of prayer to aspects of development is more effective than not using interactive multimedia recognition of prayer on aspects of development.